O futuro é a semana que vem: um estudo sobre juventude e tempo - Nogueira, Flávia Maria Marques (2016)
Considering all the contemporary scenarios of a dynamic world in which several transformations have occurred over the last decades, we noticed that modern day life rhythms have changed and intensified, and this fact is related to the speed of technological times. Due to these changes and following the temporal acceleration the social institutions have also changed, the subjects, and their life styles. In this contemporary logic, we verify that one of the great transformations that we witnessed in society and the stratospheres of life of the subject is associated to the social dimension of time. There is a different time in our historical moment, there is a time made up of new mediations and, therefore, it is lived in a different way. The subjects live new relations to time, the experience of speed, a result of the capitalist social life, that demands more productivity every time. As well as this, there is also living time of the instantaneousness, of the immediate, of the ephemeral, moderated by the time of the virtual, ultimately the time of new technologies, the time of the internet. So taking into consideration the changes that contemporaneity has inflicted on its subjects, and that it brings a determinate experience of time, we have as a general objective on this study research how young people are establishing their future projects mediated by contemporary time. To ensue that, the theoretical referential method used is of the Psychosocial History, which is based on historical dialectic materialism. An instrument of incomplete phrases was developed, composed of phrases related to future time, to future projects, about work, about adults, and about the technological times for young people. The instrument was applied in 31 young people, students of the third year of medium grade in private schools in the city of Sao Paulo, and students of pre-“vestibular” schools, also private. The analysis enabled seizing that, at this age of uncertainty, young people seek certainty, objectivity, and immediate answers. With that we can say that the fundamental contemporary rule is to try to obtain security in the movement. To try to obtain security in uncertainty and unpredictability, not having a long deadline as a horizon. Following that argument, we could observe that to elaborate long-term projects sound too vague for them. They bring to us the fact that they have goals to be achieved, they do have objectives, but on a discourse that seems empty, undefined, inconsistent, because “getting there” is still a too distant future. The subjects of this research have demonstrated the great pressure that they have suffered over present time, they feel like they have been “swallowed”, by the immediacy of their studies, the intense preparation for the “vestibular”, by the short time constraints they have at their disposal for their choices. Therefore, the more they are prisoners of the present, the less they own their own futures, and that ends up making it harder for them to build their projects. We understand then that at our present juncture immediate achievements are valued in detriment of long-term achievements, because the future is immediate. The future is now